Strategies for Social Inference A Similarity Contingency Model of Projection and Stereotyping in Attribute Prevalence Estimates. (article). - Ames, Daniel R.
Most model of how perceivers infere the widespread attitudes and qualities of social groups revolve around either the self (social projection, false consensus) or stereotypes (stereotyping). The author suggest people rely on both of these inferential strategies, with perceived general similarity moderating their use , leading to increase levels of projection and decreased levels of stereotyping. Three studies featuring existing individual differences in perceived similarity as well as manipulated perceptions supported the predictions, with similarity yielding increased projection to, and decreased stereotyping of various in- group and out-groups. Evidence that projection and stereotyping may serve as influential alternatives also emerged. The model and accompanying results have implications for research and social comparison and projection, stereotyping and prejudice, and social inference. -- (from the author).
Keywords: Psychology-Periodicals.